Social Media Marketing, Product Quality, and Viral Marketing Effects on Scarlett Skincare Purchase Decisions with Brand Awareness as Mediator : Pemasaran Media Sosial, Kualitas Produk, dan Efek Pemasaran Viral terhadap Keputusan Pembelian Scarlett Skincare dengan Kesadaran Merek sebagai Mediator - Nia Rofiana; Sutono; Gilang Puspita Rini (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2026)
Purchase decisions are an important indicator of the success of marketing strategies in the skincare industry. Understanding the factors that influence consumer purchase decisions is essential for companies to strengthen competitiveness and build sustainable customer relationships. This study aims to examine the influence of social media marketing, product quality, and viral marketing on the purchase decisions of Scarlett skincare products, with brand awareness acting as a mediating variable. This research uses a quantitative approach with an associative design. The population of this study consists of consumers who have used or purchased Scarlett skincare products. The sample was determined using purposive sampling based on specific criteria related to product usage experience. Data were collected through an online questionnaire using a Likert scale. The data were analyzed using Structural Equation Modeling (SEM) with AMOS to test the measurement and structural models. The results indicate that social media marketing, product quality, and viral marketing have a positive influence on brand awareness. Furthermore, these variables also positively affect consumers’ purchase decisions. Brand awareness also plays a mediating role in strengthening the relationship between marketing activities, product quality, and consumer purchase decisions. These findings support the Stimulus–Organism–Response (SOR) theory, which explains that external marketing stimuli and product attributes influence consumer responses through internal cognitive processes such as brand awareness.